(untitled) (The Journal of Medicine, Humanity and Media, 2023)
The 6th 6th International Conference of "Medicine, Humanity and Media", hosted by the School of Journalism and Communication of Peking University, was successfully held from November 3 to 5, 2023. Nearly a hundred participants from over thirty universities at home and abroad joined the event, engaging in rich and constructive discussions around the theme of "Health Communication in the Process of Digitalization".